Efficacy and tolerability of topiramate-augmentation therapy for schizophrenia: a systematic review and meta-analysis of randomized controlled trials - Okuyama Y; Oya K; Matsunaga S; Kishi T; Iwata N (Neuropsychiatric Disease and Treatment)
Yuji Okuyama,* Kazuto Oya,* Shinji Matsunaga, Taro Kishi, Nakao Iwata Department of Psychiatry, Fujita Health University School of Medicine, Toyoake, Japan *These authors contributed equally to this work Abstract: This study aimed to perform a comprehensive meta-analysis of topiramate-augmentation therapy in patients with schizophrenia receiving antipsychotic agents. Data published up to June 20, 2016 were obtained from the PubMed, PsycINFO, and Cochrane Library databases. Twelve randomized controlled trials comparing topiramate to placebo or antipsychotic only were included (n=676 patients). The primary outcome was change in overall symptoms. Relative risk (RR) and standardized mean difference (SMD), along with 95% confidence intervals, were calculated using random effects model for each outcome. Topiramate-augmentation therapy was superior to the control for decreasing overall symptoms (SMD -0.55, 95% confidence interval -0.86 to -0.24; P=0.001; I2=55%, eight comparisons, n=380), positive symptoms (SMD -0.4), negative symptoms (SMD -0.47), and Positive and Negative Syndrome Scale general subscale scores (SMD -0.67). Furthermore, topiramate-augmentation therapy decreased weight (SMD -0.69) and body mass index (SMD -0.95) compared with the control. Topiramate was similar to the control with respect to discontinuation due to all causes (RR 1.19), inefficacy (RR 1.71), and adverse events (RR 1.09). Topiramate was associated with higher incidence of paresthesia (RR 2.67) and attention difficulty (RR 8.97) compared with the control. Our results seemed to suggest that topiramate-augmentation therapy improves the psychopathology of schizophrenia with good tolerability and has the additional advantage of weight maintenance. However, because there were some limitations (numbers of studies and patients included in the meta-analysis were small, some studies used completer analysis, Chinese studies were included in the meta-analysis, and studies that had a risk of bias were included in the meta-analysis) in this study, we cannot apply the results of this study in daily clinical practice. Keywords: schizophrenia, topiramate, efficacy, safety, systematic review, meta-analysis